DEIKSIS DALAM FILM GODâ€™S NOT DEAD 2 KARYA HAROLD CRONK : ANALISIS PRAGMATIK - RUGIAN, FRECELIANA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT This research is entitled â€œDeiksis dalam Film Godâ€™s Not Dead 2 Karya Harold Cronkâ€. The aims of this research are to identify and classify the types of deixis and to analyze the usage of deixis in the film Godâ€™s Not Dead 2 by Harold Cronk. The method used in this research is descriptive method. The data of deixis have been taken from the sentences in the film Godâ€™s Not Dead 2. The data were analyzed based on Levinson theory.Â  The result of this research shows that are five types of deixis in the film Godâ€™s Not Dead 2, those are person deixis (first person : I, we, our, my, me, us, ours, myself, and mine ; second person : you, your, and youself ; and third person : she, himself, they, her, him, them, his, he, and their), place deixis : here, field, locker room, parking, sidewalk, class, home, in front of, church, classroom, there, coffee shop, campus, and hospital, time deixis : tonight, this day, 2.000 years ago, last 3 months, 5 minutes, many years earlier, after years, during, other night, and two days, discourse deixis : this, that, it, and those, and social deixis : junior, low man, juror, Your Honor, the touchtone, client, waiter, historic figure, young lady, hostile witness, ladies, gentleman, and Father. Whereas the usage of deixis found in the film Godâ€™s Not Dead 2 are symbolic and gestural usage.Â  It is expected that this research will help the students and the other readers in learning the pragmatic aspects, especially about deixis. Keywords : Pragmatics, Deixis, Film, Godâ€™s Not Dead 2